Youth sport injury research: a narrative review and the potential of interdisciplinarity - Hausken-Sutter, S. E.; Pringle, R.; Schubring, A.; Grau, S.; Barker-Ruchti, N. (BMJ Open Sport & Exercise Medicine, 2021)
To prevent sports injuries, researchers have aimed to understand injury aetiology from both the natural and social sciences and through applying different methodologies. This research has produced strong disciplinary knowledge and a number of injury prevention programmes. Yet, the injury rate continues to be high, especially in youth sport and youth football. A key reason for the continued high injury rate is the development of injury prevention programmes based on monodisciplinary knowledge that does not account for the complex nature of sport injury aetiology. The purpose of this paper is to consider and outline an interdisciplinary research process to research the complex nature of sport injury aetiology. To support our proposition, we first present a narrative review of existing youth football and youth sport injury research demonstrating an absence of paradigmatic integration across the research areas` main disciplines of biomedicine, psychology and sociology. We then demonstrate how interdisciplinary research can address the complexity of youth sport injury aetiology. Finally, we introduce the interdisciplinary process we have recently followed in a youth football injury research project. While further research is necessary, particularly regarding the integration of qualitative and quantitative sport injury data, we propose that the pragmatic interdisciplinary research process can be useful for researchers who aim to work across disciplines and paradigms and aim to employ methodological pluralism in their research.